2008
DOI: 10.1002/pros.20782
|View full text |Cite
|
Sign up to set email alerts
|

A methyl‐deficient diet modifies histone methylation and alters Igf2 and H19 repression in the prostate

Abstract: These findings highlight the plasticity of the epigenome in an epithelial organ vulnerable to neoplastic change. They further suggest that chromatin modifications are more susceptible to methyl-deficient diets than DNA methylation at this locus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 46 publications
1
53
0
Order By: Relevance
“…Moreover, lack of DNA methylation in the ICR of IGF2/H19 together with no detectable level of dimethyl H3K9 in PCa might provoke binding of CTCF to this region resulting in enhanced expression of H19, the role of which in carcinogenesis is still unclear. Interestingly, recent study from Dobosy et al (31) provided evidence that folateand methyl-deficient diet causes decrease in di-methyl H3K9 modification within H19 promoter in prostate tissue of mature mice which also has been observed in our ChIP assay on human PCa tissue. Further studies investigating the relationship between DNA methylation, chromatin structure and DNA accessibility will provide insights into the epigenetic regulation of the IGF2/H19 locus in PCa.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, lack of DNA methylation in the ICR of IGF2/H19 together with no detectable level of dimethyl H3K9 in PCa might provoke binding of CTCF to this region resulting in enhanced expression of H19, the role of which in carcinogenesis is still unclear. Interestingly, recent study from Dobosy et al (31) provided evidence that folateand methyl-deficient diet causes decrease in di-methyl H3K9 modification within H19 promoter in prostate tissue of mature mice which also has been observed in our ChIP assay on human PCa tissue. Further studies investigating the relationship between DNA methylation, chromatin structure and DNA accessibility will provide insights into the epigenetic regulation of the IGF2/H19 locus in PCa.…”
Section: Discussionsupporting
confidence: 82%
“…Hypomethylation of IGF2 P3 is responsible for upregulated IGF2 transcription and has an active role in osteosarcoma and hepatoblastoma (12,27). Several clinical studies have shown a positive correlation between plasma DHA concentration and erythrocyte folate level or serum vitamin B 6 and B 12 , reported to be methylation modulators of imprinted genes (25,47,49). Interestingly, a choline-and methionine-deficient diet revealed a decrease of repressive dimethylation at histone H3 lysine 9 (H3K9) within H19 promoter as well as Igf2 P2 and P3 (6).…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have shown a positive correlation between plasma DHA concentration and erythrocyte folate level or serum vitamin B 6 and B 12 , reported to be methylation modulators of imprinted genes (25,47,49). Interestingly, a choline-and methionine-deficient diet revealed a decrease of repressive dimethylation at histone H3 lysine 9 (H3K9) within H19 promoter as well as Igf2 P2 and P3 (6). We found that DHA had a much stronger effect on hypomethylation of IGF2 P3, in accordance with findings from Ba et al (1) in preterm infants, and maternal DHA supplementation has shown a preventive effect of longer gestational duration (3).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being an essential amino acid, Met is also the precursor of SAM, which is required for polyamine synthesis and for various methylation processes, including DNA cytosine methylation and histone methylations. In mammals, which lack de novo folate synthesis, a Met-deficient diet causes locus-specific reduction of H3K9me2 levels (Dobosy et al, 2008), and genetic disruption of folate utilization for 5-methylTHF synthesis correlates with genomic DNA hypomethylation (Friso et al, 2002). The folate biosynthesis pathway is essentially the same in plants as in bacteria (Basset et al, 2005;Hanson and Gregory, 2011), both using dihydropterote synthase for dihydropteroic acid production.…”
Section: Discussionmentioning
confidence: 99%